The potential of Sonneratia caseolaris mangrove leaves extract as a bioactive food ingredient using various water extract [version 4; peer review: 2 approved] - Maharani Pertiwi Koentjoro; Bambang Semedi; Ike Listya Anggraeni; Hartati Kartikaningsih; Nur Fitriana (F1000Research)
Background Sonneratia caseolaris, has been widely utilized by the Indonesian. S. caseolaris leaves contain various active compounds, contributing to their popularity in the treatment of various diseases. Mangrove leaves are also known to exhibit very high antioxidant activity. This study aims to assess the antioxidant activity of S . caseolaris leaves extracted using different solvents. The resulting extract was evaluated for antioxidant activity by the 2,2-diphenyl-1-picrylhydrazyl radical scavenging activity (DPPH) techniques. Methods Analysis of total flavonoids, total phenols, identification of active compounds with Liquid Chromatography High Resolution Mass Spectrometry (LC-HRMS), and bioinformatics were also carried out to obtain temporary conclusions about the antioxidant activity of S. caseolaris leaf extract. Results The results indicated that S. caseolaris leaves extracted with methanol and distilled water exhibited the highest antioxidant activity compared to other extracts. The analysis of total flavonoids and total phenols yielded results consistent with the antioxidant activity tests. LC-HRMS results identified three compounds in all S. caseolaris leaf extracts with antioxidant activity, namely TEMPO, Choline, and Betaine. TEMPO demonstrated a higher antioxidant activity than Choline and Betaine, as indicated by the binding affinity values in the bioinformatics analysis. Conclusions It is evident that S. caseolaris leaf extracts has the potential to serve as an effective antioxidant agent. Further research is needed to confirm how the potential compounds in S. caseolaris leaf water extracts interact with the target protein Keap1. This research aims to utilize S. caseolaris as active components in food products, thereby enhancing antioxidant consumption among consumers.